2011
DOI: 10.4067/s0716-078x2011000300006
|View full text |Cite
|
Sign up to set email alerts
|

Near-shore distribution of phyllosomas of the two only lobster species (Decapoda: Achelata) present in Robinson Crusoe Island and endemic to the Juan Fernández archipelago

Abstract: Two lobster species coexist in the southeast Pacifi c Juan Fernández archipelago, Jasus frontalis (Milne-Edwards, 1837) and Acantharctus delfi ni (Bouvier, 1909). Like most lobster species they undergo a prolonged larval period, which is particularly long for J. frontalis (> 16 months). Though typical of Palinurids, this long larval duration is usually not thought to be conducive to local recruitment. While it is known that settlement is confi ned to the three islands of the archipelago (Robinson Crusoe, Aleja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
1
5
0
2
Order By: Relevance
“…Zooplankton surveys carried out during different field campaigns have also explored the pelagic environments around the Archipelago (e.g. Acuña et al, 2009;Landaeta & Castro, 2004;Palma et al, 2011;Rivera & Mujica, 2004a), and reported a similar group of species and abundances compared to those recorded here (i.e. with amphipods, ostracods, and decapod larvae exhibiting the higher numbers).…”
Section: Pelagic Assemblages In Rci Rocky Reefssupporting
confidence: 66%
See 1 more Smart Citation
“…Zooplankton surveys carried out during different field campaigns have also explored the pelagic environments around the Archipelago (e.g. Acuña et al, 2009;Landaeta & Castro, 2004;Palma et al, 2011;Rivera & Mujica, 2004a), and reported a similar group of species and abundances compared to those recorded here (i.e. with amphipods, ostracods, and decapod larvae exhibiting the higher numbers).…”
Section: Pelagic Assemblages In Rci Rocky Reefssupporting
confidence: 66%
“…Even although cryptic fauna can account for up to two thirds of the reef's richness and are crucial components of regional biodiversity and conservation studies regarding the design of marine protected areas (Pearman et al, 2018), information on their biology and ecology in isolated south-east Pacific environments remain unexplored. Around the Juan Fernandez Archipelago and the RN Ecoregion, various efforts have increased knowledge in some of these cryptic components at both, the community level (Gusmao et al, 2018) as well as in specific taxonomic groups, including crustaceans (Meerhoff, Mujica, García, & Nava, 2017;Palma et al, 2011;Rivera & Mujica, 2004a, 2004b, fish (Acuña, Cabrera, & López, 2009;Landaeta & Castro, 2004), and molluscs (Cárdenas, Viard, & Castilla, 2008;Carrasco, Meerhoff, Yannicelly, & Ibáñez, 2019). Therefore, a different scenario may emerge when considering smaller and poorly studied organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Tubbs et al [ 20 ] suggested an optimal temperature of 17.5 °C for the in vitro fecundity of Z. seriolae because egg production decreases at other temperatures yet sexual maturity is reached more quickly at higher temperatures. The seawater in NCC varies between 18 °C and 20 °C in summer [ 77 ] and between 14 °C (winter-autumn) and 20 °C (spring-summer) in the waters of JFA [ 78 ]. Therefore, it is possible that the local environmental conditions can modify the biological traits of Z. seriolae populations across the SEP; however, it is also possible that genetic differences among the parasite populations are reflected in different biological traits.…”
Section: Discussionmentioning
confidence: 99%
“…El acoplamiento de estos factores reproductivos con las condiciones oceanográficas y meteorológicas imperantes en el período de liberación larval, es relevante en términos de la posible capacidad advectiva o de retención que podrían caracterizar al sistema de archipiélagos en este período. Palma et al (2011) indican que la baja abundancia de larvas tempranas de J. frontalis encontrada en varias zonas cercanas a la costa, durante el período de liberación larval, podría depender de los niveles de advección que caractericen a las corrientes. El aporte de estos factores reproductivos al éxito del asentamiento está determinado principalmente por la sobreposición espacio-temporal que existe entre ellos y los factores oceanográficos imperantes en las Tabla 3.…”
Section: ) Y Más Elevados (unclassified